Management Contracts and Water Utilities : The Case of Monagas State in Venezuela - Mariño, Manuel; Stein, John; Wulff, Fransico (World Bank, Washington, DC, 2012)
The management contract for water and sanitation services in the Venezuelan state of Monagas, awarded in early 1997 to a Spanish firm, is one of very few signed and active management contracts in the water sector. Management contracts pose design challenges. Their built-in incentives do not include equity at risk, so surrogate incentives must be designed, such as a performance bonus. Deciding how to award these contracts is also a challenge, because they lie somewhere between technical assistance (which should be awarded on the basis of skill and experience) and a lease (which should be awarded on the basis of price). It is too early to say whether management contracts can evolve into a more high-powered form of private participation like a concession. But the early operational results are very positive, and the experience sheds light on when a management contract is the right choice, how it should be designed to introduce the right incentives for the contractor and the public representatives, and what steps to take in awarding it.